La técnica del Sociodrama en la enseñanza aprendizaje aplicada en la asignatura de Lengua y Literatura en niños/as de tercero de educación básica de la Escuela Fiscal Mixta 28 de Mayo periodo lectivo 2016 - Gavilanes Guaman, Ana María (2016)
Under the title "THE TECHNIQUE OF THE SOCIODRAMA IN THE LEARNING TEACHING APPLIED IN THE SUBJECT OF LANGUAGE AND LITERATURE IN CHILDREN OF THIRD PARTY OF BASIC EDUCATION OF THE FISCAL MIXED 28 MAY SCHOOL". The present project of educational intervention is structured, presenting in option to obtain the title of Graduate in Sciences of the Education, in the Faculty of Sciences of the Education, Social, Philosophical and humanistic of the State University of Bolivar. For its logical structure we started with the description of the problem, helping us graphically of the technique "Tree of problems", where we start from the central problem, the same one that is disaggregating the causes, effects of the problem related to it. The theoretical-practical basis, the basis for the intervention, was obtained from a critical analysis reflective to the answers given by teachers, parents, through the survey conducted to each of the elements of the educational community. Once the problem is analyzed, the matrix of the logical framework is elaborated, a tool that allows to establish with clarity the structure and relation between problems, the objectives and the development of each one of its operative components. Below is a breakdown of each of the three components, which are designed according to those involved in the problem, and therefore are the solution to the problem, namely the components are; Teachers (component one), students (component two), and parents (component three) The design of each of the components is summarized in an array and then the objective tree is presented, which is the positive result of the Problem Tree and a basis for deriving the conclusions. Concludes this work with the basic bibliography used and the. That has been considered more important.